Dynamic Local Usage: An Accurate Model for Usage of Tile-Internal Wiring in Global Routing - Bihler, Tilmann; Blankenburg, Daniel (2025 62nd ACM/IEEE Design Automation Conference (DAC), 2025)
Traditional global routing simplifies routing as a Steiner Tree packing problem on a grid graph, often neglecting the need to account for tile-internal wiring connections to pin shapes. Local wiring usage is typically pre-estimated, leading to inaccuracies. To address this gap, we introduce the Dynamic Local Usage (DLU) model, which evaluates wiring usage based on exact wire shapes and optimizes routes up to detailed pin shapes. Key innovations include tip-to-tip penalty extensions to accurately model packing density and new algorithms to optimize routes according to the DLU congestion model. We demonstrate the superiority of the Dynamic Local Usage model by comparing results after global and detailed routing to an industrial global router on the 3 nm and 5 nm technology nodes. Our model achieves significant improvements in the number of vias, scenic routes, design rule violations, and timing metrics after detailed routing. Furthermore, the DLU provides a better support for incremental design changes, such as pin movements, by dynamically updating local wiring usage during routing.